Community Nurses Are Important Providers of Continuity of Care for Patients With Chronic Diseases: A Qualitative Study - Jinjin Ge PhD; Yongfang Zhang BA; Enfang Fan BA; Xi Yang BA; Liping Chu BA; Xiaoling Zhou MA; Yuzhong Yan PhD; Weiqun Liu MA (SAGE Publishing, 2023)
To clarify the functional orientation of community health nurses in the continuous care of patients with chronic diseases and to encourage community nurses to play their expected roles in extended nursing work. In this study, conducted from May to July 2020, the staff of Shanghai Community Health Service Center were sampled, and representative medical staff were selected for in-depth interviews and focus group discussions. Eighteen community medical staff members participated. The functions of community nurses in the continuous care of patients with chronic diseases are mainly as follows: ① undertaking individualized projects for patients' continuous treatment, nursing and rehabilitation; ② creating "peer education" conditions for patients; ③ providing supportive care to family caregivers; and ④ participating in the whole process of family doctor team health management. The results provide a reminder for nurse managers that under the new mission, community nurses need "one specialty and multiple abilities," appropriate nursing technology and good health management skills. The training of community nurses should better meet the practical needs of patients with chronic diseases.